Texts on the Move. Ricezione della scrittura femminile in Finlandia e Russia 1840-2020. - Capkova Viola (Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università di Napoli L’Orientale, 2022)
The project Texts on the Move aims at mapping the reception of Russian women writers in Finland as well as the reception of Finnish (both Finnish and Swedish speaking) women authors in Russia. ‘Reception’ is understood broadly, including not only translations, but also other ways in which texts have been moving and reacted at transnationality, highlighting a wide range of literary, cultural, and social networks. The project offers a new look at literary history and cultural exchange between Finland and Russia, seen in a broader European context. It connects to digital research methods as well as to research on digital media, methods and topics that have developed in the field of gender studies over the last decades. It introduces numerous ways of mesoanalysis and mixed methods. It is the first large-scale research project on the history of Finnish-Russian literary relations from the gender viewpoint. The project is funded by the Emil Aaltonen Foundation, Finland.